Upaya Pengelolaan Abu Hasil Pengolahan Limbah Medis Dengan Stabilisasi/Solidfifikasi (S/S) Di Indonesia: Sebuah Review - Andina Ilma Darmawan; Mega Mutiara Sari; I Wayan Koko Suryawan (Jurnal Serambi Engineering, 2022)
The generation of medical waste in Indonesia is increasing with the increase in health services to the community. Medical waste in Indonesia must be processed so as not to pollute the environment. One of the efforts made by medical waste producers is the thermal process in the form of incineration. This paper examines efforts to manage medical waste by incineration, especially the ash produced. The ash produced is very dependent on the efficiency of combustion where the results of combustion by the incinerator can be in the range of 78.23 – 99.99%. While the operating temperature of the incinerator at 800-1600ºC. The characterization of incineration ash focuses more on TCLP (Toxicity Characteristic Leaching Procedure), especially heavy metals. Heavy metals in the ash showed that Pb and Zn did not meet the quality standards. Stabilization/Solidification (S/S) is a commonly used method to reduce the hazardous nature of incineration medical ash waste. The S/S process provides a barrier generated at the surface of the effluent to limit the migration of contaminants through mechanical processes or chemical reactions between the ash and cement. The time required for this process is up to 28 days.